2011
DOI: 10.1111/j.1540-5850.2011.00979.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure of State‐Level Tax and Expenditure Limits

Abstract: While much consideration has been given to the approval process, base classification, and codification of tax and expenditure limits (or TELs), these factors tell us nothing about how they actually work. This study focuses exclusively on the technical elements of these limits and finds how states estimate their limits have over time eroded their potency. More specifically, if a state resets or rebases its limit annually by using actual revenues or expenditures for the preceding year, the limit will trend close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 0 publications
0
46
0
Order By: Relevance
“…It was not until 1934 that Arkansas adopted the first state-level TEL (Kioko & Martell, 2012). While New Jersey passed a TEL in 1976 (Kioko, 2011), the beginning of the recent tax limitation movement is generally attributed to Howard Jarvis and the "People's Initiative to Limit Property Taxation," or Proposition 13 in California (Mullins & Wallin, 2004). This initiative was closely followed by Michigan's Headlee Amendment, Massachusetts' Proposition 2½, Missouri's Hancock Amendment, and others (Atchison, 1992;Fino, 2003;McGuire & Rueben, 2006;Mullins & Wallin, 2004;Waisanen, 2008;Wallin, 2004).…”
Section: History Of Telsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not until 1934 that Arkansas adopted the first state-level TEL (Kioko & Martell, 2012). While New Jersey passed a TEL in 1976 (Kioko, 2011), the beginning of the recent tax limitation movement is generally attributed to Howard Jarvis and the "People's Initiative to Limit Property Taxation," or Proposition 13 in California (Mullins & Wallin, 2004). This initiative was closely followed by Michigan's Headlee Amendment, Massachusetts' Proposition 2½, Missouri's Hancock Amendment, and others (Atchison, 1992;Fino, 2003;McGuire & Rueben, 2006;Mullins & Wallin, 2004;Waisanen, 2008;Wallin, 2004).…”
Section: History Of Telsmentioning
confidence: 99%
“…Kioko and Martell (2012) found that stricter TELs were associated with higher state aid. Kioko (2011) found that TELs with general fund limits transfer more state funds to local governments because, she argued, the general fund limits are set so high that they are not binding. When there are both a state and local TEL, state aid to local governments is higher.…”
Section: Local-level Researchmentioning
confidence: 99%
“…The most important design issues are spending category exemptions, the basis for the cap on the growth of state spending/revenues, and whether "re-basing (see below)" (Kioko, 2011) occurs if actual spending or revenue falls short of the cap amount. Seventeen states have TEL caps based on some measure of personal income, typically annual, or average annual, rate of growth in personal income.…”
Section: 0mentioning
confidence: 99%
“…Six states link their TEL to spending as a share of personal income. When TEL caps linked to personal income are binding, the instability in personal income growth results in volatility in state spending over the business cycle (Crain, 2003;Holcombe and Sobel 1997;Kioko, 2011;Krol, 2007;Mitchell, 2010;Mullins and Wallin, 2004;Schunk and Woodward, 2005;Shadbegian, 1996;Wagner and Elder, 2005;Waisenen 2010). And the tax base of some states keeps personal income growthbased TELs from being binding very often.…”
Section: 0mentioning
confidence: 99%
See 1 more Smart Citation